Friendships, trust and advertisers: The art of mining social networks - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
The exponential growth of social networking sites over the past few years has not escaped the attention of business and government leaders, many of whom are now scrambling to uncover how best to exploit social interactions online for monetary or political gains. However, before any benefit can be realised and reaped, patterns in the relationships between users on these networks need to be analysed and understood; and to do that, there is a need to first unearth and organise data. Academics and industry practitioners exchanged their findings at a recent School of Information Systems workshop.